Electrical conductivity of undoped, singly doped, and co-doped ceria - Singh N.K.; Singh P.; Kumar D.; Parkash O. (My University, 2025)
In order to investigate the effect of single doping and co-doping on the enhancement of ionic conductivity in ceria (CeO 2), CeO 2 and a few compositions in the system Ce 0. 85Sm 0. 15 - xGd xO 1. 925 (x = 0. 00, 0. 06, 0. 09, and 0. 15) were prepared using citrate-nitrate auto-combustion method. Gels were characterized by simultaneous differential thermal analysis and thermogravimetric analysis to confirm the formation of end product from the precursor. All the compositions were found to be single-phase solid solution from their X-ray diffraction pattern. Complex plane impedance analysis clearly revealed the contribution of grains, grain boundaries, and electrode specimen interface to the total value of the resistance. The value of activation energy, E a, of conduction shows that the conduction process is mainly due to diffusion of O 2- ions through oxygen vacancies. Effect of doping has been analyzed using the concept of radius mismatch and effective index reported earlier in the literature. © 2011 Springer-Verlag.